TERPENOIDS FROM SALVIA-SCLAREA - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1994)
From an acetone extract of the whole plant Salvia sclarea, seven known diterpenes, sclareol, manool, salvipisone, ferruginol, microstegiol, candidissiol and 7-oxoroyleanone, and two new ones, 2,3-dehydrosalvipisone and 7-oxoferruginol-18-al, as well as two sesquiterpenes, caryophyllene oxide ind spathulenol, alpha-amyrin, beta-sitosterol and the flavonoids apigenin, luteolin, 4'-methylapigenin, 6-hydroxyluteolin-6,7,3',4'-tetramethyl ether, 6-hydroxy apigenin-7,4'-dimethyl ether were obtained. The diterpenoids and the sesquiterpenoids were tested for antimicrobial activity against standard bacterial strains and a yeast. 2,3-Dehydrosalvipisone, sclareol, manool, 7-oxoroyleanone, spathulenol and caryophyllene oxide were found to be active against Staphylococcus aureus, the first and third compound against Candida albicans and the last compound against Proteus mirabilis.
Keywords: SALVIA SCLAREA; LABIATAE; SESQUITERPENES; DITERPENES; TRITERPENES; FLAVONOIDS; ANTIMICROBIAL ACTIVITY; ABIETANE DITERPENOIDS